Analysis of the Sustainability of Beef Cattle Breeding Business-Intensive Rearing Patterns in, Indramayu Regency, West Java - Sutrisno; L. Cyrilla E. N. S. D.; B. W. Putra (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
The increase population growth may cause an increase in the need for food originating from animal protein, one of which is meat. The demand for beef is not matched by an increase in the national cattle population or productivity. Policies on cattle breeding in the future require basic information, potential resources, and supporting facilities that are actualized in indicators and aspects of sustainability. The aim of the study was to analyze the index and status of the sustainability of a cattle breeding business with an intensive rearing pattern in Situ Bolang Indramayu, West Java, which was assessed from ecological, socio-cultural, economic, legal-institutional, and technological-infrastructure indicators. The method used is multidimensional scaling (MDS) with the Rap-UPTS approach for the analysis of index values and sustainability status. The identification of sensitive indicators, errors in index values, and sustainability in each aspect was carried out by Leverage and Monte Carlo analysis. The respondents amounted to 12 farmers. The results of the sustainability index analysis illustrate that the ecological indicators are 66.39, socio-cultural 57.14, economic 56.31, and legal-institutional 57.44, with a fairly sustainable status. In the Technology-Infrastructure Indicator 45.48, the status is less sustainable. It is necessary to increase the status of sustainability in the future, and it is necessary to make efforts to improve overall in all sensitive aspects of increasing the status of cattle breeding areas.